Stationary distributions of fading evolutions - Pogorui, A. О. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We study fading random walks on the line. We determine stationary distributions of the fading Markov evolution and investigate the special semi-Markov case where the sojourn times of the renewal process have Erlang distributions.